Innovations in higher education : igniting the spark for success - Hoffman, Allan M. (Allan Michael); Spangehl, Stephen D. (Lanham, Md. : Rowman & Littlefield Publishers, 2012)
"Rising costs, increasing global competition, intensifying calls for accountability--all these pressures are bearing down upon the status quo of higher education today. Governments, funders, students, and parents are demanding strategic improvements in all aspects of postsecondary education. Reform cannot happen slowly--colleges and universities must take a rapid and dynamic approach to change. The answer lies in innovation, as this book shows, to promote fresh ideas and bring higher education professionals together to effect real and dramatic change"--Provided by publisher.
Part I.A view from the top -- The evolution of higher education -- Perspectives on innovation -- Does accreditation inhibit innovation? -- Measuring success -- The present state of higher education -- Community colleges -- Part II. Success : In their own words -- Academic quality measures -- Benchmarking -- Faculty development -- Student retention -- Curriculum development -- Technology -- Facilities -- Part III. Putting it all together -- Motivating success -- Building the capacity for change through innovation.
Includes bibliographical references and index.
Keywords: Education, Higher -- United States; Educational innovations -- United States; Educational change -- United States; EDUCATION -- Higher; Education, Higher..; Educational change..; Educational innovations..; United States..